A inovação schumpeteriana na produção de açúcar orgânico : a Usina São Francisco (UFRA) e o manejo agroecológico - Moraes, Marcelo Lopes de (2010)
The model imposed by the Green Revolution brought social and environmental problems that resulted in economic problems for countries in which it was introduced, including Brazil. In parallel with the oil crises of 1973/79, the Brazilian government implemented the National Program of Alcohol - ProAlcohol, which decreased the oil dependence, but on the other hand, presents problems related to sustainability. Given this, the schools that make up sustainable agriculture have become alternatives to the model-based pesticides, where the organic sugar cane meets the best practices of sustainability. Using Schumpeter as a mainly theory the objective of this work is to understand how the Plant San Francisco - UFRA entered the innovation of organic sugar in their domestic production and international markets, contributing to the sustainable development process. It is conclude that the UFRA has characteristics of Schumpeter's theory related to innovations, especially with regard to the innovative entrepreneur, the conditions for the emergence of innovations and attracting imitators. Moreover, it is possible to say that the model developed which provided a comparative advantage over competitors, anticipated the changes now occurring in the industry.